Analysis of the Management of School Operational Assistance Funds (BOS) Towards Transparency of Financial Reporting at Sdit Al Hikmah - Divas Perdana, Friga; Dali, Rahmat Mulyana; Dali, Yudiana (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2023)
The purpose of this study was to analyze whether the management of BOS (School Operational Assistance) funds was in accordance with Permendikbud Number 1 of 2018 concerning Technical Instructions for School Operational Assistance (BOS). This research is a qualitative descriptive study. The location of this research is SDIT Al Hikmah. Data collection techniques used are through observation and interviews. The data analysis technique used is descriptive data analysis. The results of the study show that: Other supervision is regular reporting every three months by schools to the Education Office regarding the use of BOS funds and information about the use of BOS funds during meetings with school committees and parents of studentsKeywords: BOS funds, planning, implementation and supervisio.